Comparative Analysis of Labor Market Dynamics Using Markov Processes : An Application to Informality - Bosch, Mariano; Maloney, William F. (2012)
This paper discusses a set of statistics for examining labor market dynamics in developing countries and offers a simple search model that informs their interpretation. It then employs panel data from Argentina, Brazil and Mexico to generate a set of preliminary stylized facts about patterns of sectoral transition and duration. Finally, it nests two competing views of the informal sector within the model and uses variation in the statistics across age and the business cycle to help discriminate between them. The results suggest that a substantial part of the informal sector, particularly the self-employed, corresponds to voluntary entry, although informal salaried work may correspond more closely to the standard queuing view, especially for younger workers.